Pemberdayaan UMKM Melalui Sosialisasi dan Pelatihan Pembukuan Keuangan Sederhana pada UMKM Kampung Kue RW 09 Kelurahan Menur Pumpungan - Maulita Ayubi Rachma; Ratih Mukti Azhar (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role as a driving force for the Indonesian economy. Kampung Kue Menur UMKM is no exception, which has business potential to develop. However, there are several obstacles faced by MSMEs that can interfere with their development. According to the results of a survey conducted by interviewing MSMEs, it can be seen that there are obstacles to their financial management. The difficulties of MSMEs in preparing simple bookkeeping and determining product selling prices are the main problems faced by MSMEs. Therefore, there is a need for socialization and simple financial bookkeeping training for MSMEs. So that with this dedication, it can be aimed at helping the SMEs of Kampung Kue Menur improve their ability to manage their business finances by carrying out simple financial bookkeeping. The results of the dedication carried out are that MSMEs realize and implement financial bookkeeping in their businesses that have a very important positive impact on businesses such as measuring their business performance, being able to separate personal and business finances, and managing business finances easily.